Age-friendly cities, knowledge and urban restructuring. Issue 1 (2nd January 2022) - Murtagh, Brendan; Cleland, Claire; Ferguson, Sara; Ellis, Geraint; Hunter, Ruth; Rodriguez Añez, Ciro Romelio; Becker, Leonardo Augusto; Hino, Adriano Akira Ferreira; Reis, Rodrigo Siqueira
ABSTRACT: Age-friendly cities and communities have emerged as a significant policy, participative and governance response to ageing and its spatial effects. This paper argues that it has important benefits in mobilizing older people, placing age on the urban agenda and building recognition across politicians, policy makers and programme managers. Based on the experience of Belfast (UK), the analysis suggests, however, that it needs to be understood within wider urban restructuring processes, the importance of the property economy and how planning practices favour particular groups and modes of development. Drawing on demographic data, policy documents and in-depth interviews, it evaluates the relationship between age and urban regeneration, research-based advocacy and central-local relations in health and place-based care. The paper concludes by highlighting the importance of knowledge in competitive policy arenas and the need to focus on the most excluded and isolated old and where and how they live.